Interleukin-1 Gene Variability and Plasma Levels in Czech Patients with Chronic Periodontitis and Diabetes Mellitus - Petra Borilova Linhartova; Hana Poskerova; Marie Tomandlova; Jirina Bartova; Katerina Kankova; Antonin Fassmann; Lydie Izakovicova Holla (Hindawi Limited, 2019)
Recent studies have suggested a bidirectional relationship between chronic periodontitis (CP) and diabetes mellitus (DM). Immunoregulatory factors such as cytokines play an important role in etiopathogenesis of both diseases. The aim of this study was to analyze variability in interleukin-1 (IL-1) gene cluster and IL-1β plasma levels in patients with CP, DM, and a combination of both diseases. A total of 1016 individuals participating in this case-control study-225 healthy controls, 264 patients with CP, 132 with type 1 diabetes (T1DM), and 395 patients with type 2 diabetes (T2DM)-were genotyped using methods based on polymerase chain reaction for IL-1 gene polymorphisms (IL-1A (−889C/T, rs1800587), IL-1B (+3953C/T, rs1143634), and IL-1RN (gene for IL-1 receptor antagonist, IL-1RA, 86 bp tandem repeats in intron 2)). Levels of IL-1β were measured by Luminex methods in subgroups of controls, CP, T1DM + CP, and T2DM + CP subjects. Although no significant associations were found in the genotype and allele frequencies of IL-1A (−889C/T), significant differences in the allele frequencies of IL-1B (+3953C/T) were observed between controls and CP patients (P<0.05). In T1DM patients, IL-1RN∗S "short" allele and IL-1RN 12 genotype were significantly less frequent than those in controls (P<0.01). In haplotype analysis, TTL haplotype decreased the risk of CP development (P<0.01), whereas CCS and CTL haplotypes (P<0.01 and P<0.05) were associated with T1DM. Although IL-1β levels were measured significantly higher in mononuclear cells after stimulation by mitogens, HSP70, or selected periodontal bacteria than in unstimulated cells, IL-1 genotypes did not correlate with circulating IL-1β levels. In the Czech population, significant associations between the IL-1B polymorphism with CP and the IL-1RN variant with T1DM were found. Haplotype analysis suggests that variability in IL-1 gene cluster may be one of the factors in the CP and T1DM pathogenesis, although single variants of these polymorphisms are not substantial for protein production.